Analisis Penyajian Laporan Keuangan Pemerintahan Kabupaten Langkat - Dian Irmawani; Nila Rosdiana; Budi Dharma (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Accounting made to present or compile government financial reports has the principles of government accounting standards. Where government accounting standards exist in Government Regulation No.24 of 2005. The results of the performance of a regional government in one accounting period are referred to as government financial reports. The existence of a financial report in a government has become something that must be prepared by regional governments every year, because with a report you can find out the financial condition of a region, whether it is receipts or expenditures, every budget given by the State to a government, to compile a government must also following the structure or provisions of government laws and regulations related to financial reports. Then the method used by researchers in this analysis is descriptive analysis. Data obtained from analysis by conducting interviews, observations in the financial sector, making notes and documents with objects to be analyzed relating to the preparation of financial reports for the Langkat district government. Then the results obtained from the research are that Langkat Regency has prepared financial reports in accordance with Government Regulation No. 24 of 2005 regarding the Government Accounting System (SAP). The result is that Langkat district presents regional financial reports caused by supporting factors where these supporting factors are human resources and other supports. Supporting factors influence whether or not the results of government financial reports are good because if the understanding of employees or human resources is low, it is possible that the results obtained will not be optimal.